The effect of intrawound vancomycin powder on surgical site infection in inguinal lymph node dissection: a randomized controlled trial pilot study - Jessica B. DiSilvestro; Emily Zitek; Katina Robison; Jasmine Ebott; Corinne Jansen; Katrin Eurich; Cara Mathews; Paul DiSilvestro; Matthew Oliver; Ashley Stuckey; Katherine Miller; Elizabeth Lokich (Gynecologic Oncology Reports)
Background: Inguinal lymph node dissections are morbid surgeries with high rates of postoperative wound infections. The primary objective of this pilot study was to assess the feasibility of implementing a randomized controlled trial to assess the impact of intrawound vancomycin powder on postoperative complications after inguinal lymph node dissection in patients with vulvar cancer. Secondary objectives included 1) 30-day composite postoperative complication rate, and 2) adverse effects. Methods: This was a single-site, unblinded randomized controlled trial. Patients with vulvar cancer planning to undergo an inguinal lymph node dissection were randomized 1:1 to receive intrawound vancomycin powder at the time of surgery versus standard of care without vancomycin powder. Descriptive statistics and Chi-square were utilized. Results: Between October 2022 to May 2024, 31 patients met eligibility criteria and 30 patients enrolled (97 % recruitment rate). Three patients did not undergo surgery (90 % retention rate). All patients received their correctly assigned arm and all patients completed the postoperative follow-up (100 % adherence rate).One patient in the vancomycin group had a composite postoperative complication (hematoma), while three patients in the control arm had a complication (three inguinal surgical site infections) [8 % vs. 21 %, p = 0.32]. There were no postoperative infections identified in the patients who received intrawound vancomycin powder. No adverse events occurred with the application of vancomycin. Conclusion: This pilot study showed that this was a feasible trial with high recruitment, retention and adherence rates. The data supports proceeding with a larger trial to further elucidate the impact of this low-cost intervention.Trial Registration: ClinicalTrials.gov Identifier: NCT05625373.